Prevention of catheter-associated urinary tract infection: implementation strategies of international guidelines - Andrade, Vera Lúcia Fonseca (2021)
Objective: to describe strategies used by health professionals on the implementation of the Centers for Disease Control and Prevention guidelines for the prevention of urinary infection related to catheterism. Method: systematic review on literature based on data from CINAHL®, Nursing & Allied Health Collection, Cochrane Plus Collection, MedicLatina, MEDLINE®, Academic Search Complete, ACS - American Chemical Society, Health Reference Center Academic, Nursing Reference Center, ScienceDirect Journals and Wiley Online Library. A sample of 13 articles was selected. Results: studies have highlighted the decrease of urinary tract infection related to catheterism through reminder systems to decrease of people submitted to urinary catheterism, audits about nursing professionals practice and bundles expansion. Conclusion: the present review systemizes the knowledge of used strategies by health professionals on introduction to international recommendations, describing a rate decrease of such infection in clinical practice.